ANALYSIS OF THE IMPACT OF SIGNS OF INTENTIONAL BANKRUPTCY ON THE ECONOMIC STABILITY OF ENTERPRISES: AN ECONOMIC-ANALYTICAL APPROACH - BODNAR, Tetyana; KUSHTA, Sergiy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is dedicated the financial, managerial, and regulatory risks arising from intentional bankruptcy and their impact on the overall state of the enterprise are examined. The research confirms that intentional bankruptcy not only undermines the economic stability of individual companies but also creates significant threats to the country's business climate, undermining investor confidence and complicating the development of partnership relations in financial and economic operations.The article also provides recommendations for preventing intentional bankruptcy. The proposed risk management strategies include thorough monitoring of financial indicators, conducting regular internal audits, and implementing early warning systems for potential financial difficulties. Methods to enhance transparency and integrity in financial activities involve establishing clear financial procedures and policies, a system of internal controls, and engaging independent auditors.Future research prospects in this field may include the development of more detailed methodologies for the early detection of signs of intentional bankruptcy, studying the impact of legislative and regulatory measures, and analyzing the effects of such cases on specific economic sectors and regions. Ultimately, it is essential to explore the effectiveness of corporate policies and internal control mechanisms in preventing intentional bankruptcy, which will contribute to strengthening the economic stability of enterprises.
Keywords: intentional bankruptcy; economic stability; financial stability; asset outflow; reduced investment; operational risks; liquidity; solvency; credit rating; loss of qualified personnel; production and sales; corporate governance; financial transparency; internal audit; regulatory measures